THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND SELF-CARE MANAGEMENT AND QUALITY OF LIFE TYPE 2 DIABETES MELLITUS PATIENTS (Proceedings OPTIMAL, 2024)
Type 2 diabetes mellitus is a disease characterized by increased blood sugar levels. Diabetic mellitus patients often experience a low quality of life. This decline in quality of life is usually caused by the lack of family support and the patient's inability to manage self-care. Quality of life is important to receive serious attention because a decrease in the patient's quality of life will worsen the patient's disease and increase the mortality rate. This study aims to determine the relationship between family support, self-care management, and patients' quality of life with type 2 diabetes mellitus. This study is quantitative research using a cross-sectional approach. The number of samples in this study was 49 people using the purposive sampling technique. The chi-square test results on the relationship between family support and the quality of life of type 2 diabetes mellitus patients obtained a p-value = 0.000. In contrast, the relationship between self-care management and the quality of life of type 2 diabetes mellitus patients obtained a p-value = 0.000 (p